Double balloon enteroscopy-assisted endoscopic retrograde cholangiopancreatography in Roux-en-Y gastric bypass anatomy: expert vs. novice experience - Kashani, Amir; Abboud, Gebran; Lo, Simon K.; Jamil, Laith H. (Endoscopy International Open, 2018)
Background and study aims Double-balloon enteroscopy-assisted endoscopic retrograde cholangiopancreatography (DBE-ERCP) in post-Roux-en-Y gastric bypass (RYGB) patients is a technically challenging procedure. We aimed to determine the success rate of DBE-ERCP performed by a novice to the procedure in post-RYGB after training with an expert. Patients and methods Medical records for 103 consecutive post-RYGB patients who underwent DBE-ERCP in a tertiary center were retrospectively reviewed. The procedures were performed by Operator A (18 years of high-volume ERCP practice before acquiring DBE skill in 2004), and operator B ( < 2 years’ experience in DBE and ERCP). ERCP success rate and time in patients with an intact papilla were compared between Operator A’s first and last sets of cases in equal number to the cases performed by Operator B. Results A total of 129 DBE-ERCPs were performed (Operator A: 109; Operator B: 20) over an 80-month time span. Among patients with an intact papilla, DBE-ERCP success rates for Operator A’s first (87.5 %) and last (92.9 %) 20 cases were similar to that of Operator B (92.9 %) (P = 1.00 for both). Mean of DBE-ERCP time for the last 20 cases of Operator A was (100 minutes; 95 % confidence interval: 81,123) less than that for operator B (176 minutes; 95 % confidence interval: 138,224) (P = 0.01). Overall adverse events rates were 11 % and 5 % for Operators A and B, respectively (P = 0.69): pancreatitis (n = 10), cholangitis (n = 1), and perforation (n = 2); all were mild and treated conservatively. Conclusions Despite the intrinsic technical difficulty, DBE-ERCP can be successfully and safely performed in post-RYGB patients by an endoscopist proficient in both conventional DBE and ERCP. Ideally, this endoscopist should observe several cases of DBE-ERCP performed by an expert to learn the techniques.